A Flexible Approach for the Calibration of Biplanar Radiography of the Spine on Conventional Radiological Systems - Daniel C. Moura (2010)
This paper presents a new method for the calibration of biplanar radiography that makes possible performing 3D reconstructions of the spine using conventional radiological systems. A novel approach is proposed in which a measuring device is used for determining focal distance and have a rough estimation of translation parameters. Using these data, 3D reconstructions of the spine with correct scale were successfully obtained without the need of calibration objects, something that was not previously achieved. For superior results, two optional steps may be executed that involve an optimisation of the geometrical parameters, followed by a scale adjustment with a very simple calibration object. Computer simulations with in vivo CT data show RMS 3D reconstruction errors of 1.9 mm when under the maximum expected variation of the geometrical parameters of the radiological system. Simulations also show that the 3D spinal length may be accurately calculated, but with superior results when using optimisation and adjusting scale (RMS error of 2.09 mm). In vitro experiments with a dried spine composed by 17 vertebrae show mean 3D reconstructions errors of 1.7 mm. We conclude that the proposed method is suitable for use in clinical environment, and that it compares favourably with previous calibration techniques.